2009
DOI: 10.1038/eye.2008.431
|View full text |Cite
|
Sign up to set email alerts
|

23-Gauge transconjunctival sutureless pars plana vitrectomy: results of a prospective study

Abstract: Purpose To evaluate results of 23-gauge transconjunctival sutureless vitrectomy in various indications of vitreoretinal diseases. Design Prospective, non-comparative study. Materials and methods Fifty-seven consecutive eyes of 57 patients underwent vitreoretinal surgery by one surgeon using the 23-gauge, two-step instrumentation developed by Dutch Ophthalmic Research Center Inc., for epiretinal membranes (n ¼ 24), macular holes (n ¼ 10), diabetic retinopathy (n ¼ 4), rhegmatogenous retinal detachment (n ¼ 3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 31 publications
(35 reference statements)
1
16
0
1
Order By: Relevance
“…All of them resolved spontaneously in 1 week, which was also the most common complication in our series. Schweitzer et al observed postoperative hypotony in 21.1% of their cases; postoperative hypotony was the most common complication in their series also (10). Postoperative hypotony was observed in 6.5% of cases in Gupta et al 's series and 3.4% in Chieh et al 's series (3,5).…”
Section: Discussionmentioning
confidence: 95%
“…All of them resolved spontaneously in 1 week, which was also the most common complication in our series. Schweitzer et al observed postoperative hypotony in 21.1% of their cases; postoperative hypotony was the most common complication in their series also (10). Postoperative hypotony was observed in 6.5% of cases in Gupta et al 's series and 3.4% in Chieh et al 's series (3,5).…”
Section: Discussionmentioning
confidence: 95%
“…In 23-gauge transconjunctival sutureless vitrectomy, the incidence of postoperative hypotony varies between 2.6 and 22.8% [27,39,52,53,54,55,56]. In the 25-gauge one, this incidence has a mean of 13% between articles [7,57,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The use of small sutureless incisions has greatly reduced the surgically induced astigmatism, and this is no longer a matter of concern in small gauge vitrectomy (Kadonosono et al 2006;Schweitzer et al 2009). We did not observe a significant surgically induced astigmatism in our study.…”
Section: Discussionmentioning
confidence: 99%